2008
DOI: 10.3174/ajnr.a0828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carotid Artery Stenting on Cognitive Function in Patients With Carotid Artery Stenosis: Preliminary Results

Abstract: BACKGROUND AND PURPOSE:Stenosis of the carotid artery may be a cause of reduced cognitive performance that can be ameliorated with placement of a stent. The goal of this study was to measure cognitive performance and speed of psychomotor performance prospectively before and after carotid stent placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 36 publications
3
29
0
3
Order By: Relevance
“…However, at 1 year after CAS, the scores improved significantly (P Ͻ .01). The 1-year results showed long-term improvements in neural function in patients treated with CAS, and the results were similar in Turk et al, 34 who analyzed 3-month follow-up scores.…”
Section: Discussionsupporting
confidence: 85%
“…However, at 1 year after CAS, the scores improved significantly (P Ͻ .01). The 1-year results showed long-term improvements in neural function in patients treated with CAS, and the results were similar in Turk et al, 34 who analyzed 3-month follow-up scores.…”
Section: Discussionsupporting
confidence: 85%
“…Cognitive improvement after carotid artery stenting (CAS) has been reported in some recent studies, but the basis for this improvement is still poorly understood [1,2,3]. Recently, Yamada et al [4] reported a case of partial reversal of leukoaraiosis (LA) (approximately 10% lesion load) shortly after CAS, and this reversal may account for cognitive improvement after CAS and potentially attests to the clinical importance of LA and its subsequent regression after CAS [4,5].…”
Section: Background and Purposementioning
confidence: 99%
“…Recently, Yamada et al [4] reported a case of partial reversal of leukoaraiosis (LA) (approximately 10% lesion load) shortly after CAS, and this reversal may account for cognitive improvement after CAS and potentially attests to the clinical importance of LA and its subsequent regression after CAS [4,5]. From the fact that LA extent is a good index of hypoperfusion-induced vascular dementia, Markus et al [6] postulated that endovascular stent placement in the carotid artery can restore cerebral perfusion and thereby reduce LA [2,6]. …”
Section: Background and Purposementioning
confidence: 99%
“…The improvement in cerebral perfusion after CAS, as documented by imaging technologies (Ko et al, 2005;Martin, A. J. et al, 2005;Tavares et al, 2010;Van Laar et al, 2007), has also been documented through questionnaires for dementia that show clinical improvement in scores after CAS (Moftakhar et al, 2005;Takaiwa et al, 2009;Turk et al, 2008). …”
Section: Wwwintechopencommentioning
confidence: 98%